L’objectif homonormatif de Virginie Despentes Bye Bye Blondie, du texte à l’écran - Dobrenn, Audrey (Romanica Silesiana)
Virginie Despentes’ Homonormative Lens. Bye Bye Blondie, from Text to Screen When she adapted her novel Bye Bye Blondie for the cinema, Virginie Despentes decided to switch the central heterosexual love story between Gloria and Eric to a homosexual love story between Gloria and Frances. However, she refused to offer another heteronormative lesbian scene. Instead, she tends to bring a homonormative representation of female love to the French mainstream cinema, and develops the systems of a new esthetic. No erotic scene, no representation of the couple according to a feminine/masculine logic, Despentes puts on screen a love story into which no spectator is allowed a voyeuristic glance. Key words: Despentes, Bye Bye Blondie, homonormative, lesbian cinema.